2021
DOI: 10.3389/fnbot.2021.755723
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Control of Visually-Guided Movements in a 3D-Printed Robot Arm

Abstract: The control architecture guiding simple movements such as reaching toward a visual target remains an open problem. The nervous system needs to integrate different sensory modalities and coordinate multiple degrees of freedom in the human arm to achieve that goal. The challenge increases due to noise and transport delays in neural signals, non-linear and fatigable muscles as actuators, and unpredictable environmental disturbances. Here we examined the capabilities of hierarchical feedback control models propose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The difficulty with this explanation is that low-pass filters distort the input signal by introducing amplitude modulation and phase lags – filtered trajectories in Schaal and Sternad (2001), Gribble and Ostry (2003) and Matic et al (2021) all show that output ellipses have a different size than input ellipses. Participants in experiment 1 generally maintained the size of the cursor trajectory equal to that of the target’s trajectory, and followed the targets without phase lags – similar results were found by Viviani and Mounoud (1990) when tracking ellipses and by Parker (2020) when tracking one-dimensional sine waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty with this explanation is that low-pass filters distort the input signal by introducing amplitude modulation and phase lags – filtered trajectories in Schaal and Sternad (2001), Gribble and Ostry (2003) and Matic et al (2021) all show that output ellipses have a different size than input ellipses. Participants in experiment 1 generally maintained the size of the cursor trajectory equal to that of the target’s trajectory, and followed the targets without phase lags – similar results were found by Viviani and Mounoud (1990) when tracking ellipses and by Parker (2020) when tracking one-dimensional sine waves.…”
Section: Discussionmentioning
confidence: 99%
“…Schaal and Sternad (2001) found that even a simple Butterworth filter with an appropriate cutoff frequency can produce power-law trajectories out of constant-speed trajectories. Recently, we have shown that a robot arm following a constant-speed visual target can also produce power law trajectories because it behaves as second order system with delay, also a low-pass filter (Matić et al, 2021). Similarly, as recognized by Lacquanity et al (1983), an ellipse composed of pure sinewave components, without any harmonics, will conform to the −1/3 speed-curvature power law.…”
Section: Discussionmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. (Barter & Yin, 2021;Matić et al, 2021;Young, 2017). Importantly, the main tenets of PCT have received wide empirical support (for a review, see Mansell, 2020).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…A series of studies involving PCT models that control perceptual variables—retinal linear velocity and lateral displacement—closely match real-world movement data during object interception without requiring prediction (Marken, 2021). Furthermore, software that implements perceptual control systems in robots permits effective navigation and obstacle avoidance (Young, 2017), balance (Johnson et al, 2020), locomotion on four legs (Barter & Yin, 2021), and arm coordination (Matić et al, 2021). These robots exhibit simple, naturalistic, purposive behavior through the real-time control of perceptual input, without the need for prediction, or consciousness.…”
Section: Scientific Backgroundmentioning
confidence: 99%
See 1 more Smart Citation